Cline: A new decision-tree family - Amasyali, M. Fatih; Ersoy, Okan (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2008)
A new family of algorithm called Cline that provides a number of methods to construct and use multivariate decision trees is presented. We report experimental results for two types of data: synthetic data to visualize the behavior of the algorithms and publicly available eight data sets. The new methods have been tested against 23 other decision-tree construction algorithms based on benchmark data sets. Empirical results indicate that our approach achieves better classification accuracy compared to other algorithms.
Keywords: classifier combination; decision forests; decision trees; learning (artificial intelligence); machine learning; multivariate decision trees; pattern classification; pattern recognition; SELECTION; Computer Science; Engineering